HUBUNGAN ANTARA MODAL INTELEKTUAL DENGAN NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Lita Lada Antana; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2017)
ABSTRACTThis study aims to analyze the relationship of intellectual capital with the component ofHCE (human capital efficiency), SCE (structure capital efficiency), and CEE (capital employedefficiency) to market value proxies with M / B (market to book value) and also ROA (Return onassets). Source of data in the form of company's financial statements obtained from theIndonesia Stock Exchange website, where the samples taken are manufacturing companies listedon the Indonesia Stock Exchange (BEI) in 2013-2015. Sample determination method used ispurposive sampling, the result of this research indicate that Return On Asset influenced byHuman Capital Efficiency, Structural Capital Efficiency, and Capital Efficiency Employed equalto 29,3%.Keywords: Intellectual capital relationship, HCE (human capital efficiency), SCE(structure capital efficiency), and CEE (market employee efficiency) M / B(market to book value), ROA (return on assets).